If it's not what You are looking for type in the equation solver your own equation and let us solve it.
=Y-3
We move all terms to the left:
-(Y-3)=0
We get rid of parentheses
-Y+3=0
We add all the numbers together, and all the variables
-1Y+3=0
We move all terms containing Y to the left, all other terms to the right
-Y=-3
Y=-3/-1
Y=+3
| 17x=-8x | | 0.05(x+60)−0.07(x−50)=6.3 | | 1.5x-7=3.5 | | (2x-11)(7x+15)=0 | | -11b-+7=40 | | 14y-9=2y+27 | | 22-r=4r-8 | | 7x+21=4x-8 | | 3x+4(2)=8x | | 5(v+5)=3v+45 | | 17x-9=7x+9 | | 3x+5=-5x=6x-12 | | 4+10x=46 | | 10a+4=-16 | | 2y-4=6(y-4) | | g2=3.15 | | 6(u-3)=9u+3 | | 6x+4(-3x+2)=-52 | | 5x+11-6=540 | | 5x+5=540 | | 8p-3=5p+33 | | 6h-34=-6h+1 | | 3x+3x=162 | | −7/10w-18=51/5w | | 8b+16=-5b-2 | | 8+4x=1-4x | | 3(4x+2)=20x=9x+2 | | 27+20=12x | | 8v+5(3+2v)=-40+7v | | 3m-6=-12+12m | | 7x+5(x+3)=3 | | 0.9p-3=0.6 |